RAR-Based Prognostic Model for Predicting Overall Survival in Hepatitis B Virus-Related Hepatocellular Carcinoma: A Multicenter Study - Tan M; Liu Y; Dai W; Chen Y; Cai D; Chen B; Wang J; You R; Li D; Huang H (Journal of Inflammation Research)
Maoqing Tan,1,* Yifan Liu,2,3,* Wei Dai,1,* Yanling Chen,4 Danni Cai,1 Baomin Chen,3 Jing Wang,1 Ruolan You,1 Dongliang Li,5 Huifang Huang1 1Central Laboratory, Fujian Medical University Union Hospital, Fuzhou, Fujian, 350001, People’s Republic of China; 2First Central Clinic Institute, Tianjin Medical University, Tianjin, People’s Republic of China; 3Department of Hepatobiliary Surgery, The First Affiliated Hospital of Sun Yat-Sen University, Guangzhou, Guangdong, 510000, People’s Republic of China; 4Department of Hepatobiliary Surgery and Fujian Institute of Hepatobiliary Surgery, Fujian Medical University Union Hospital, Fuzhou, Fujian, 350001, People’s Republic of China; 5Department of Hepatobiliary Disease, Fuzong Clinical Medical College of Fujian Medical University (900TH Hospital of Joint Logistics Support Force), Fuzhou, Fujian, 350025, People’s Republic of China*These authors contributed equally to this workCorrespondence: Huifang Huang, Central Laboratory, Fujian Medical University Union Hospital, 29 Xinquan Road, Fuzhou, Fujian, 350001, People’s Republic of China, Tel +8613365910318, Fax +86 591-87113828, Email huanghuif@fjmu.edu.cn Dongliang Li, Department of Hepatobiliary Disease, 900TH Hospital of Joint Logistics Support Force, Xi Er Huan Bei Road, Fuzhou, Fujian, 350025, People’s Republic of China, Tel +8613665052006, Fax +86 591-22859128, Email dongliangli93@163.comPurpose: Hepatitis B virus-related hepatocellular carcinoma poses a significant global health challenge. This study aimed to develop and validate a novel prognostic nomogram integrating the red blood cell distribution width-to-albumin ratio for predicting patients’ overall survival.Patients and Methods: A retrospective cohort of 1403 patients was divided into training, internal validation, and external validation cohorts. A multivariate Cox regression model selected variables to construct a nomogram and an online calculator, which were subsequently validated.Results: The ratio emerged as an independent risk factor for long-term survival (hazard ratio: 5.808, 95% confidence interval: 1.721– 19.599). A prognostic nomogram incorporating nine variables based on the ratio was developed. Calibration curves demonstrated high concordance between the predicted and actual 3-year survival rates. Decision curve analysis indicated that the nomogram significantly increased the net benefit of predicting 3-year survival. Based on the area under the receiver operating characteristic curves, the nomogram outperformed traditional models in predicting survival across the three cohorts. Patients were stratified into low-, intermediate-, and high-risk groups based on risk scores calculated from the nomogram. In all cohorts, the median survival time of the high-risk group was significantly shorter than that of the intermediate- and low-risk groups. An online calculator, deployed via a web-based platform, facilitated convenient mortality risk prediction for these patients.Conclusion: The ratio-based nomogram we developed can accurately predict the survival of patients with hepatitis B virus-related hepatocellular carcinoma, serving as an effective auxiliary tool for clinical personalized treatment and prognostic assessment. Keywords: albumin, hepatitis B virus-related hepatocellular carcinoma, nomogram, prognosis, red blood cell distribution width